Production of Obionin A and Derivatives by the Sooty Blotch Fungus Microcyclospora malicola - Surup, Frank; Medjedović, Ajda; Schroers, Hans-Josef; Stadler, Marc (Planta Medica, 2015)
A multitude of sooty blotch and flyspeck fungi, mainly belonging to the Ascomycetes order Capnodiales, causes dark blemishes and flyspeck-like spots on apples worldwide. Different sooty blotch and flyspeck fungi can coexist in the same orchard and even on a single fruit. Our preceding experiments revealed an activity of Microcyclospora malicola strain 1930 against the anthracnose fungus Colletotrichum fioriniae in dual culture assays. Extracts of M. malicola strain 1930 showed a broad bioactivity against filamentous fungus Mucor hiemalis and gram-positive bacterium Bacillus subtilis. A bioactivity-guided isolation led to the identification of obionin A (1) as the main active principle. In addition to 1, which was previously isolated from the marine fungus Leptosphaeria obiones, we isolated three derivatives. Metabolite 2 bears a keto function at C-6, besides the replacement of oxygen by nitrogen at position 10. Two more derivatives are adducts (3, 4) of acetone as work-up artifacts. Because obionin A (1) and its derivative 2 showed cytotoxic effects and antifungal activities, we propose a role of these secondary metabolites in the antagonism between M. malicola and other apple colonizing sooty blotch and flyspeck fungi, other epiphytes, or apple pathogens competing for the same ecological niche.
Keywords: Microcyclospora malicola strain 1930; sooty blotch and flyspeck; plant disease; microbial interactions; secondary metabolites; natural products; structure elucidation